Internalization of Environmental Care Character through Science Learning in Elementary School Students in East Lombok - Lia Rismawati; Muh. Jaelani Al Pansori; Qodri Mursyidin (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
This study aims to describe the process of internalizing the environmental care character through science learning in elementary schools in East Lombok, covering its planning, implementation, and the supporting and inhibiting factors. The research employed a qualitative approach with a descriptive case study design. Informants comprised classroom teachers, principals, and fifth-grade students selected purposively. Data were collected through participant observation, in-depth interviews, and documentation, using observation guides, interview guides, and documentation checklists as instruments. Data were analysed using the interactive model of Miles and Huberman consisting of data reduction, data display, and conclusion drawing, while validity was ensured through source and technique triangulation and member checking. The findings reveal that internalization occurred through three interrelated stages—moral knowing, moral feeling, and moral action—actualised in habituation, direct environmental observation, and project-based activities, and reinforced by Sasak local wisdom. Environmental care was manifested in waste sorting, plant care, and water conservation. Teacher role-modelling and the school green culture were the primary supporting factors, whereas limited facilities and inconsistent habituation were the main inhibiting factors. The study concludes that contextual and culturally grounded science learning effectively internalizes the environmental care character.